2005
DOI: 10.1111/j.1365-2672.2005.02555.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and safety aspects of enterococci from slightly fermented sausages

Abstract: Aims: To determine the biodiversity of enterococci from slightly fermented sausages (chorizo and fuet) at species and strain level by molecular typing, while considering their safety aspects. Methods and Results: Species-specific PCR and partial sequencing of 16S rRNA and sodA genes were used to identify enterococcal population. Enterococcus faecium was the most frequently isolated species followed by E. faecalis, E. hirae and E. durans. Randomly amplified polymorphic DNA (RAPD)-PCR revealed species-specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
4
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 67 publications
3
44
4
3
Order By: Relevance
“…This prevalence of putative virulence factors is common among food-animal enterococci [46,49]. The virulence data for E. faecalis are also consistent with the hypothesis that the flies acquired E. faecalis from sludge.…”
Section: Discussionsupporting
confidence: 74%
“…This prevalence of putative virulence factors is common among food-animal enterococci [46,49]. The virulence data for E. faecalis are also consistent with the hypothesis that the flies acquired E. faecalis from sludge.…”
Section: Discussionsupporting
confidence: 74%
“…These results are similar to previous reports of Abriouel et al (1) regarding the absence of the cylA gene among vegetable food isolates. High rate of asa1 and cylA genes among our E. durans isolates is a worrying output as there are some reports suggesting that the presence of virulence traits in species other than E. faecalis and E. faecium is important for proper evaluation of virulence evolution within the Enterococcus genus (16,23). No significant difference was observed between cylA gene positivity and β-hemolytic activity in our study.…”
Section: Discussioncontrasting
confidence: 47%
“…Finally, other researchers revealed that Enterococcus spp. strains from different sources could have the ability to reach the intestinal lumen and stay alive in that environment [28,47] However, further in vitro studies are needed with these strains in order to establish their probiotic potential. …”
Section: Screening For Probiotic Potentialmentioning
confidence: 99%